Manifested Style of Leadership Influencing Instructors’ Satisfaction in a Vocational College in Chengdu, China - Tan, Luyuan (Pacific International Journal, 2025)
This study explored the manifested leadership styles of school administrators and their influence on instructors’ job satisfaction at Chengdu Vocational and Technical College of Industry and Trade in Chengdu, China. Specifically, it examined how instructors’ demographic profiles—sex, age, educational attainment, and length of service—related to their perceptions of four leadership styles: authoritative, democratic, facilitative, and situational. The study employed a quantitative-descriptive method, utilizing survey questionnaires administered to 231 faculty members. Findings revealed that respondents perceived all four leadership styles as only slightly evident in current administrative practices, with the authoritative style being the most apparent, followed by facilitative, situational, and democratic styles. Furthermore, statistical analysis showed no significant differences in the respondents’ assessments of leadership styles when grouped according to their demographic profiles. These findings suggest a shared and consistent perception of school leadership regardless of demographic differences, highlighting the need for more intentional and visible leadership practices to enhance instructor satisfaction within the institution.